The Effect of a Single High Dose of Vitamin D on Serum Levels of Its Metabolites in the Elderly - Dorota Leszczyńska; Alicja Szatko; Konrad Kowalski; Dorota Raczkiewicz; Magdalena Ostrowska; Waldemar Misiorowski; Wojciech Zgliczyński; Piotr Glinicki (Frontiers in Bioscience-Landmark, 2022)
Background: Vitamin D is a dietary micronutrient responsible for calcium and phosphorus metabolism and multiple extraskeletal actions. The assessment of vitamin D status is commonly based on measurement of 25(OH)D total concentration in serum. However, the usage of liquid chromatography with tandem mass spectrometry (LC-MS/MS) technique allows to reliably assess a panel of vitamin D metabolites in serum or plasma, which may help to investigate the metabolic paths of vitamin D, especially in populations at risk of deficiency. Methods: A randomized, two-arms, open study was conducted on 58 patients (28 female and 30 male; aged from 61 to 96 years old). The primary aim was to assess the effects of a single, high, oral dose of vitamin D3 (120,000 IU) on serum 25(OH)D3, 25(OH)D2, 24,25(OH)2D3, 3-epi-25(OH)D3, 1,25(OH)2D3, 24,25(OH)2D3/25(OH)D3 ratio, and 25(OH)D3/3-epi-25(OH)D3 ratio concentration (measured by LC-MS/MS) at baseline, 3 days and 7 days after administration, compared to control group. The secondary aim was assessment of influence of percentage of fat tissue on serum metabolites of vitamin D and their changes after bolus dose. Results: 56.6% study group attained a serum 25(OH)D3 concentration >30 ng/mL. All subjects, except for one patient achieved a serum 25(OH)D3 concentration >20 ng/mL after administration. No one exceed reference value of vitamin D (30–50 ng/mL). Among participants who received vitamin D3 there were significant increase in 25(OH)D3, 3-epi-25(OH)D3, 1,25(OH)2D3, 24,25(OH)2D3 on 3rd day after administration. 24,25(OH)2D3 concentration gradually grew, achieving the highest concentration on 7th day. The percentage increase of 25(OH)D3 was negatively correlated with baseline 25(OH)D3 (r = –0.688, p = 0.001). Positive correlation between percentage increase in 25(OH)D3 and a percentage increase serum concentration of 24,25(OH)2D3 (r = 0.954, p < 0.001), 3-epi-25(OH)D3 (r = 8.03, p < 0.001) and 1,25(OH)2D3 (r = 0.789, p <0.001) were found. None of the study participants developed hypercalcemia. The baseline concentration of analyzed metabolites of vitamin D in serum and their percentage increase were neither dependent on BMI nor percentage of fat tissue. Conclusions: High dose of vitamin D rapidly increases 25(OH)D3 concentration in the elderly patients. The response to the bolus of vitamin D includes activation of 3-epimerase, followed by production of 24,25(OH)2D3, which protects from excessive increase of active form of vitamin D.